Efficacy of Probiotic Supplementation on Growth Performance, Carcass Traits, and Gut Health in Meat-Type Ducks - Supranoto Supranoto; Rosidi Rosidi; Tri Sukmaningsih; Soegeng Herijanto (Journal of Sustainable Livestock, 2026)
This systematic review and meta-analysis evaluate the efficacy of probiotic supplementation on growth, carcass traits, and gut health in meat-type ducks. Adhering to PRISMA 2020 guidelines, a database search up to October 2023 identified 25 eligible studies. Data synthesis using random-effects models showed probiotics significantly improved productivity. Specifically, final body weight increased by a mean difference of 150 g (p < 0.001), average daily gain improved by 8% (SMD = 0.65), and feed conversion ratio decreased by 0.08 units. Carcass analysis indicated a 1.8% increase in dressing percentage and enhanced breast muscle yield. For gut health, probiotics increased villus height by 15%, reduced crypt depth, and modulated microbiota by boosting Lactobacillus spp. in contrast to suppressing E. coli and Salmonella. Subgroup analyses revealed that multi-strain formulations and dosages >10^8 CFU/g yielded superior outcomes. Despite moderate heterogeneity, sensitivity analyses confirmed these findings' robustness. In conclusion, integrating high-dose, multi-strain probiotics optimizes nutrient absorption, immune function, and growth, maximizing economic returns and physiological well-being in commercial duck farming.